Topical Sisomycin In The Management Of Atopic Dermatitis - Dhar Sandipan; Kanwar Amrinder J; Kohil Manjula; Ganguly Nirmal K (Wolters Kluwer Medknow Publications, 1996)
Thirty-four children (up to 12 years) with atopic dermatitis (AD) having few localized lesions of eczema were treated with topical sisomicin sulphate (0.1%). After 2 weeks of twice daily application of sisomicin, there was neither any clinical nor any bacteriological improvement. Topical sisomicin was not found to be useful in the management of AD.